Fire management effects on carbon flow from root litter to the soil community in a tallgrass prairie - Shaw, Elizabeth Ashley, author; Wall, Diana H., advisor; Cotrufo, M. Francesca, committee member; Kelly, Eugene F., committee member (Colorado State University. Libraries, 2013)
Belowground litter decomposition is a major component of carbon cycling in grasslands, where it provides energy and nutrients for soil microbes and fauna. Fire, a historically frequent disturbance and a common management tool, removes above ground biomass and litter accumulation making belowground root litter of greater importance to decomposer food webs. While many studies use biomass measures of soil faunal groups to estimate changes in soil food web structure and energy flow, little is known about the flow of C from root litter to soil microbial and nematode communities in grasslands and if biomass measures can indicate this flow of C at a fine scale. Our greenhouse experiment first investigated how C from Andropogon gerardii (big bluestem) root litter was allocated into different soil microbial and nematode groups in frequently burned (FB) and infrequently burned (IB) tallgrass prairie soil. Incorporation of 13C into microbial fatty acids and nematode communities was determined on six occasions during decomposition in order to examine whether different groups of microorganisms and fauna were specialized on the root-litter derived C. Results showed that FB and IB soils supported microbial communities of differing community composition and abundance. IB had, generally, higher microbial abundance, more strongly dominated by bacteria than FB soil. Compound-specific stable isotope ratio analysis showed that root litter-C was more quickly incorporated into FB soil microbes. By the end of the experiment, all microbial groups were more highly 13C enriched in FB soils than in IB soils, with the exception of gram-negative bacteria for which there was no significant difference between the two soils. For nematodes, there was no significant difference in abundances; however, fungivore nematodes only incorporated root litter-C in FB soil while bacterivores, omnivores and predators derived at least some C from root litter in both treatments. Despite lower abundance of microbes in FB soil, total root litter mass loss did not differ between FB and IB soil, indicating higher microbial activity in FB soil. Our results reveal that FB prairie soil food webs are more closely coupled to root litter decomposition, where root litter is of increased importance as a C and nutrient source due to the frequent removal of standing biomass and shoot litter by fire. In the second part of our greenhouse experiment, we compared soil energy channel biomass measures with C flow into the soil food web. By coupling the energy channel biomass measurement approach with our decomposition study (using stable isotope enrichment to trace the flow of C into nematode trophic groups), we compared the quantified C flow to nematode energy channel biomass measures during decomposition of 13C-labeled big bluestem root litter. We hypothesized that biomass measures for nematode bacterial and fungal energy channels would indicate the proportion of root litter derived C incorporated into each nematode energy channel. Nematode biomasses and δ13C values were assessed initially (day 0) and after 180 days of incubation. Results showed the nematode bacterial energy channel dominated over the nematode fungal energy channel in both FB and IB grasslands. Yet, FB grassland soil had significantly higher nematode bacterial energy channel biomass than IB at time 0. In both soils, the nematode bacterial energy channel biomass increased significantly after the addition of root litter and there were no differences in the nematode bacterial channel biomass between the two soils at the final harvest (180 days). There were no differences between FB and IB soil's nematode fungal energy channel biomass at either day 0 or 180 days. 13C analysis of nematodes confirmed our hypothesis, as more root litter-C was concentrated in the dominant nematode bacterial energy channel in both FB and IB grassland soils. However, the IB soil's nematode bacterial energy channel had incorporated significantly more root litter derived C than the FB soil, despite no differences in these energy channel biomasses at the final harvest. The FB soil food web showed the opposite effect for the nematode fungal energy channel. These results indicate that while energy channel biomass measurements of nematodes give a broad overview of C flow, 13C decomposition tracer studies are more precise, and provide exact measures of C flow through soil food webs for ecosystem research. Overall, our results highlight the general view that plant litter is an important C-source in grasslands and further show that root litter-C is incorporated differently in frequently and infrequently burned soil food webs. We show that frequently burned soil food webs may be more specialized to decompose grass root litter. Our results indicate the C flow within soil food webs in differing burn management areas, and show differences between the frequently and infrequently burned tallgrass prairie.
Keywords: 13C; decomposition; grassland; microbes; nematodes; soil